GD3, a prominent ganglioside of human melanoma. Detection and characterisation by mouse monoclonal antibody (The Rockefeller University Press, 1982)
Mouse monoclonal antibody AbR24 has a high degree of specificity for human melanoma cells when tested on viable cultured cells using the protein A mixed hemagglutinin serological assay. The antigen detected by this antibody has been isolated from melanoma cells and shown to be GD3 ganglioside by compositional and partial structural analysis and by comparison with authentic GD3 in thin layer chromatography (TLC). AbR24 reacts with authentic GD3, but not with any other ganglioside tested. Using TLC and reactivity with AbR24, a wide range of cells and tissues was examined for the presence of GD3. A new serological assay, termed glycolipid-mediated immune adherence, was devised for assaying the reactivity of AbR24 with gangliosides. Melanomas (cultured cells or tumor tissue) were shown to have GD3 and GM3 as major gangliosides. Other cells and tissues examined also contained GD3, but usually only in low amounts. Melanomas (and MOLT-4, a T cell line) were characterized by a simplified ganglioside profile with GD3 and GM3 as major components. The apparent discrepancy between the ubiquitous presence of GD3 and the serological specificity of AbR24 for melanoma cells can be explained in terms of localization and concentration of GD3 in different cells.